The homecoming of an Indigenous Australian diaspora as impetus for language revival: the Kaurna of the Adelaide plains, South Australia. Issue 1 (1st January 2019) - Amery, Rob
ABSTRACT: Following the invasion, or colonisation as some prefer to call it, Indigenous Australia has been characterised by plummeting populations, largely as a result of introduced diseases and the movement of peoples, following the theft of their lands and in response to colonial and subsequent Australian state and federal government policies. At times, various Aboriginal peoples were completely removed from their homelands. One such case concerns the Kaurna people of the Adelaide Plains in South Australia. Following the abandonment of restrictive policies, Aboriginal people drifted back to Adelaide and many began to identify with their Kaurna ancestry. All Kaurna people have multiple ethnicities within their ancestry, providing opportunities for shifting identities and shifting affinities. This paper investigates the role that the Kaurna language now serves for the returning Kaurna diaspora and for others in metropolitan Adelaide. Within the Kaurna community there are strong pressures for both conformity and non-conformity. We see this in relation to the Kaurna language through language planning measures on the one hand, and on the other through identity politics expressed through the language. Kaurna language is in demand by Kaurna people as a source of names and for emblematic use within the public domain. It is just beginning to make inroads into private domains as several families attempt to raise young children speaking Kaurna. The Kaurna language is also in demand by the wider community, where there is a strong and largely unmet demand for teachers of Kaurna and for Kaurna names and translations of various kinds. The Kaurna language has re-emerged from a point of almost total obscurity 30 years ago to something of an auxiliary language used alongside English. Whilst it will never replace English, it is still on the ascendency, as it addresses needs both for the returning diaspora and wider society.